High-throughput dual-colour precision imaging for brain-wide connectome with cytoarchitectonic landmarks at the cellular level - Hui Gong (Nature Portfolio, 2016)
High-throughput imaging methods for brain-wide connectome mapping with precise location reference have been lacking. Here authors report a method that allows simultaneous acquisition of fluorescently labelled neurons and cytoarchitectural landmarks in the same mouse brain at the single-cell resolution.